A Case of Congenital Nephrotic Syndrome with Crescents Caused by a Novel Compound Heterozygous Pairing of NPHS1 Genetic Variants - Kyle N. Goodman; Pongpratch Puapatanakul; Kevin T. Barton; Mai He; Jeffrey H. Miner; Joseph P. Gaut (Case Reports in Nephrology)
Congenital nephrotic syndrome is an autosomal recessive inherited disorder that manifests as steroid-resistant massive proteinuria in the first three months of life. Defects in the glomerular filtration mechanism are the primary etiology. We present a child who developed severe nephrotic syndrome at two weeks of age and eventually required a bilateral nephrectomy. Genetic testing revealed compound heterozygous variants in NPHS1 including a known pathogenic variant and a missense variant of uncertain significance. Light microscopy revealed crescent formation—an atypical finding in congenital nephrotic syndrome caused by nephrin variants—in addition to focal segmental and global glomerulosclerosis. Electron microscopy showed diffuse podocyte foot process effacement. Confocal and Airyscan immunofluorescence microcopy showed aggregation of nephrin in the podocyte cell body that is not a result of diffuse podocyte foot process effacement as seen in minimal change disease. These findings confirm the novel variant as pathogenic.